Predictors of Extended Length of Stay Following Open Reduction and Internal Fixation for Distal Radius Fractures - Smolev, Emma; Sriram, Varun; Kim, Matthew; Kennedy, John; Leatherwood, William; Komatsu, David E.; Wang, Edward D. (Journal of Wrist Surgery, 2024)
An extended length of stay (eLOS) following open reduction and internal fixation (ORIF) for distal radius fractures has been associated with increased patient morbidity and health care costs. The primary objective of this study was to identify risk factors, including patient characteristics, comorbidities, and postoperative complications, which are associated with an eLOS following ORIF for distal radius fractures.All patients who underwent ORIF for distal radius fractures between 2015 and 2021 were queried from the American College of Surgeons National Surgical Quality Improvement Program database. Postoperative complications were reported within 30 days of procedure. eLOS was defined by ≥3 days from operation to discharge. We identified a total of 26,138 patients and 5.1% (1,323) of patients had an eLOS. Multivariate logistic regression, adjusted for all significantly associated variables, was employed to identify predictors of eLOS following ORIF.Characteristics of patients significantly associated with eLOS were age ≥ 75 (p < 0.001), male gender (p = 0.006), body mass index < 18.5 (p < 0.001), American Society of Anesthesiologists (ASA) ≥ 3 (p < 0.001), dependent functional status (p < 0.001), noninsulin-dependent diabetes (p < 0.001), chronic obstructive pulmonary disorder (COPD) (p < 0.001), ascites (p = 0.005), congestive heart failure (CHF) (p < 0.001), hypertension (p < 0.001), chronic steroid use (p = 0.004), bleeding disorder (p < 0.001), and transfusion ≥ packed red blood cell (pRBC) 72 hours before surgery (p < 0.001). After controlling for significantly associated variables, predictors of eLOS were age ≥ 75 (reference < 65; odds ratio [OR]: 1.34, 95% confidence interval [CI]: 1.24–1.46; p < 0.001), ASA ≥ 3 (OR: 1.79, 95% CI: 1.54–2.01; p < 0.001), male gender (OR: 1.32, 95% CI: 1.13–1.54; p < 0.001), COPD (OR: 1.48, 95% CI: 1.15–1.91; p = 0.003), CHF (OR: 1.94, 95% CI: 1.10–3.42; p = 0.022), bleeding disorder (OR: 1.93, 95% CI: 1.45–2.58; p < 0.001), transfusion ≥ 1 pRBC before surgery (OR: 27.65 95% CI: 58.22–93.02; p < 0.001), bleeding transfusion (OR: 76.70, 95% CI: 15.13–388.81; p < 0.001), septic shock (OR: 13.31, 95% CI: 1.99–88.97; p = 0.008), and nonhome discharge (OR: 34.31, 95% CI: 28.21–41.72; p < 0.001).Age ≥ 75, ASA ≥ 3, male gender, COPD, CHF, bleeding disorder, transfusion pRBC, bleeding transfusion, septic shock, and nonhome discharge were associated with eLOS following ORIF for distal radius fractures.Level III; retrospective cohort comparison; prognosis study
Keywords: distal radius fracture; open reduction internal fixation; extended length of stay